Development of gut microbiota and bifidobacterial communities of neonates in the first 6 weeks and their inheritance from mother. (1st January 2021) - Yang, Bo; Ding, Mengfan; Chen, Yingqi; Han, Fengzhen; Yang, Chunyan; Zhao, Jianxin; Malard, Patrice; Stanton, Catherine; Ross, R. Paul; Zhang, Hao; Chen, Wei
ABSTRACT: Microbiota especially Bifidobacterium play an important role in adjusting and maintaining homeostatic balance within the infant intestine. The aim of this study was to elucidate the relationship between maternal and infant gut microbiota and identify the Bifidobacterium species that may transfer from mother to infant over the first 42 days of the infant's life. Nineteen mother-infant-pair fecal samples were collected and the diversity and composition of the total bacterial and Bifidobacterium communities were analyzed via 16S rDNA and bifidobacterial groEL gene high throughput sequencing. The results revealed that the relative abundance of Bifidobacterium was significantly higher in the infant gut while Parabacteroides, Blautia, Coprococcus, Lachnospira and Faecalibacterium were at lower relative abundance in 7-day and 42-day infant fecal samples compared to the maternal samples. The maternal gut has more B. pseudocatenulatum . In the infant group, B. breve and B. dentium relative abundance increased while B. animalis subsp. lactis decreased from days 7 to 42. Additionally, B. longum subsp. longum isolated from FGZ16 and FGZ35 may have transferred from mother to infant and colonized the infant gut. The results of the current study provide insight toward the infant gut microbiota composition and structure during the first 42 days and may help guide Bifidobacterium supplementation strategies in mothers and infants.